Effect of the Training to the Levels of the Serum Zn and Cu - Arslan, Fatma (Asian Journal of Chemistry, 2010)
The purpose of this study is to investigate serum levels of zinc and copper in well-trained male boxers during and after an anaerobic maximal exercise. Eleven well-trained young male completed the exercise protocol. Blood samples were collected before the exercise, immediately after exercise and 1 h after the exercise. Serum was analyzed for Zn and Cu by using inductively coupled plasma optical emission spectrometry (ICPOES) method. It was observed that the maximal anaerobic exercise didn't have a significant effect on the serum levels of zinc and copper in elite boxers (p > 0.05).